Comparison of the Grid and Off-Grid Hybrid Power Systems for Application in University Buildings in Nigeria - Chidiebere Diyoke; Marcel Onyekachi Egwuagu; Thomas Okechukwu Onah; Kenneth Chikwado Ugwu; Eberechukwu Chukwunyelum Dim (International Journal of Renewable Energy Development, 2023)
The Nigerian Universities rely on weak and unreliable fossil-based electric grids with diesel engine generators (DEG) as a backup. However, there is a potential to light up the campuses using power systems derived from primary renewable power systems (RPS) like wind turbine (WT) and solar photovoltaic (PV), that can be on or off-grid to improve the energy mix and duration reliably. This study presents the comparative analysis of the optimal hybrid grid and off-grid systems (OGS & OOGS) for serving the demand load of university buildings in four climatic regions of Nigeria. HOMER Pro is used to design and select the systems based on minimal net present cost (NPC) and cost of electricity (COE). The impact of a minimal renewable fraction of 95% on the optimal system architecture (OSA) and COE is studied for both grid and off-grid modes. Also, sensitivity analysis of the impact of key variables on performance for the sites is carried out. It is found that the OGS in the four regions is PV/Converter (Conv), while for the OOGS, it is PV/WT/DEG/battery (BB)/Conv except in Port Harcourt (PH), where it is PV/DEG/BB/Conv. The COE for the OGS in the Savana and monsoon climes of Enugu and PH are 10 and 19% more than that in the warm-semi arid climate zones of Maiduguri and Kano, which is approximately 0.09 $/kWh. The COE ($/kWh) for the OOGS is 0.21 in Maiduguri, 0.245 in Kano, 0.275 in Enugu and 0.338 in PH. An obligatory 95% RF changes the architecture and increases COE in all the locations except Maiduguri, with a slightly improved COE but higher NPC like other locations. It is established that the suggested hybrid system is beneficial and feasible for supplying more reliable and clean energy to educational buildings in different Nigerian locations.